Beyond Binding: The Outcomes of Antibody-Dependent Complement Activation in Human Malaria - Rathnayake, Dilini; Aitken, Elizabeth H.; Rogerson, Stephen J. (Frontiers in Immunology, 2021)
Antibody immunity against malaria is effective but non-sterile. In addition to antibody-mediated inhibition, neutralisation or opsonisation of malaria parasites, antibody-mediated complement activation is also important in defense against infection. Antibodies form immune complexes with parasite-derived antigens that can activate the classical complement pathway. The complement system provides efficient surveillance for infection, and its activation leads to parasite lysis or parasite opsonisation for phagocytosis. The induction of complement-fixing antibodies contributes significantly to the development of protective immunity against clinical malaria. These complement-fixing antibodies can form immune complexes that are recognised by complement receptors on innate cells of the immune system. The efficient clearance of immune complexes is accompanied by complement receptor internalisation, abrogating the detrimental consequences of excess complement activation. Here, we review the mechanisms of activation of complement by alternative, classical, and lectin pathways in human malaria at different stages of the Plasmodium life cycle with special emphasis on how complement-fixing antibodies contribute to protective immunity. We briefly touch upon the action of anaphylatoxins, the assembly of membrane attack complex, and the possible reasons underlying the resistance of infected erythrocytes towards antibody-mediated complement lysis, relevant to their prolonged survival in the blood of the human host. We make suggestions for further research on effector functions of antibody-mediated complement activation that would guide future researchers in deploying complement-fixing antibodies in preventive or therapeutic strategies against malaria.